Variants in calcium voltage-gated channel subunit Alpha1 C-gene (CACNA1C) are associated with sleep latency in infants. - Katri Kantojärvi; Johanna Liuhanen; Outi Saarenpää-Heikkilä; Anna-Liisa Satomaa; Anneli Kylliäinen; Pirjo Pölkki; Julia Jaatela; Auli Toivola; Lili Milani; Sari-Leena Himanen; Tarja Porkka-Heiskanen; Juulia Paavonen; et al. (PLoS ONE)
Genetic variants in CACNA1C (calcium voltage-gated channel subunit alpha1 C) are associated with bipolar disorder and schizophrenia where sleep disturbances are common. In an experimental model, Cacna1c has been found to modulate the electrophysiological architecture of sleep. There are strong genetic influences for consolidation of sleep in infancy, but only a few studies have thus far researched the genetic factors underlying the process. We hypothesized that genetic variants in CACNA1C affect the regulation of sleep in early development. Seven variants that were earlier associated (genome-wide significantly) with psychiatric disorders at CACNA1C were selected for analyses. The study sample consists of 1086 infants (520 girls and 566 boys) from the Finnish CHILD-SLEEP birth cohort (genotyped by Illumina Infinium PsychArray BeadChip). Sleep length, latency, and nightly awakenings were reported by the parents of the infants with a home-delivered questionnaire at 8 months of age. The genetic influence of CACNA1C variants on sleep in infants was examined by using PLINK software. Three of the examined CACNA1C variants, rs4765913, rs4765914, and rs2239063, were associated with sleep latency (permuted P<0.05). There was no significant association between studied variants and night awakenings or sleep duration. CACNA1C variants for psychiatric disorders were found to be associated with long sleep latency among 8-month-old infants. It remains to be clarified whether the findings refer to defective regulation of sleep, or to distractibility of sleep under external influences.